2021
DOI: 10.1039/d1ta03690d
|View full text |Cite
|
Sign up to set email alerts
|

Defining sulfonation limits of poly(ether-ether-ketone) for energy-efficient dehumidification

Abstract: Dehumidification is a vital process in the cooling industry and has emerged as a promising tool for alleviating the effects of energy-intensive activities. Advanced engineering materials, which can be employed...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
7
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 38 publications
3
7
0
Order By: Relevance
“…A broad band at 3250 cm −1 was observed which corresponds to -OH stretch. Our results are in line with the reported literature on a sulfonated brominated-PEEK polymer by Linder J Anderson et al [26,27,31,44].…”
Section: Ftir Spectrum Studiessupporting
confidence: 93%
See 3 more Smart Citations
“…A broad band at 3250 cm −1 was observed which corresponds to -OH stretch. Our results are in line with the reported literature on a sulfonated brominated-PEEK polymer by Linder J Anderson et al [26,27,31,44].…”
Section: Ftir Spectrum Studiessupporting
confidence: 93%
“…With an increase in temperature (up to 150 • C), the degree of sulfonation also reached 70% (Table 2). Akhtar et al reported that the degree of sulfonation of the SPEEK polymer was found to increase (from 3% to 46%) with an increase in the reaction time which was performed at room temperature [44]; a similar pattern of an increase in sulfonation was noted in our case for the SPEK (Table 3). A reaction with the polymer-to-sulfonating agent ratio set as 1:20 with a reaction time of 48 h (at 25 • C) gave a degree of sulfonation of ~40% which was chosen for our current study.…”
Section: Degree Of Sulfonationsupporting
confidence: 85%
See 2 more Smart Citations
“…In industry, sulfonation treatment of PEEK has been used to produce SPEEK membranes with excellent proton conductivity, and it is mainly used in fuel cells ( Montero et al, 2017 ). Sulfonation treatment of PEEK can also produce desiccants with porous structures whose surface micropores contribute to the adsorption of moisture in humid air ( Akhtar et al, 2021 ). Traditionally, sulfonation reactions require a long time at high temperature ( Yee et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%